Records of isotopic data and loess proxies over the past 130 kyr based on plant waxes preserved at Yuanbao on the western CLP - Louise Fuchs; Jingjing Guo; Enno Schefuß; Youbin Sun; Fei Guo; Martin Ziegler; Francien Peterse (PANGAEA, 2023)
This data comes from the Yuanbao section situated in the western part of the Chinese Loess Plateau at ~2180 m above sea level (35.63°N, 103,17°E), collected in August 2019 to reconstruct East Asian Monsoon climate variability. Long chain n-alkane plant waxes, magnetic susceptibility and grain size were analysed at 5 cm intervals from the upper 40 m of the loess-paleosol sequence. The section covers the past 132 ka based on the alignment of grain size and magnetic susceptibility to the quartz grain size and magnetic susceptibility records from the drill core collected at Yuanbao in 2017 (Guo et al, 2021), which were matched with the benthic δ18O record (Lisiecki and Raymo, 2005), supported by OSL data from a nearby outcrop loess-paleosol sequence (Lai and Wintle, 2006), resulting in an average resolution of our records of ~525 years. From the detected n-alkane distributions and their stable isotopic composition, records of the hydrogen isotopic composition of meteoric water (δ2Hwax), as well as of vegetation change (δ13Cwax) were generated based on the weighted mean of the isotopic composition of the most abundant plant waxes (C29 and C31 n-alkanes).